Entrepreneurial empowerment of productive families in Algeria: Its psychological and social dimensions: A study of models - Mohammad, Arzazi; Hamra, Housny (The International tax journal, 2025)
The Algerian society has recently witnessed increasing attention to issues of local development, social and economic integration, particularly through promoting the role of productive families as fundamental drivers for achieving sustainable development and eliminating unemployment and poverty, especially in rural and remote areas. This exceptional importance of the topic reflects recognition of the necessity to harness dormant human potential within households and transform it into productive forces generating income, through establishing small economic units that contribute to wealth creation and improving living conditions for families with limited income. In this context, the fundamental research problem emerges: How can productive families be empowered economically, socially, and psychologically through small projects? What are the psychological and social dimensions of this empowerment? This problematic requires an in-depth and comprehensive study combining scientific analysis with precise field observation, in order to understand the mechanisms of operation of these programs and their actual impacts on targeted groups.